Komunikasi Dakwah Karang Taruna Desa Sindanglaya dalam Membentuk Karakter Pemuda - Hendri Ruswandi (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2019)
Character building for the younger generation is crucial for the nation's and state's continuity. This study examines religious communication within the Karang Taruna organization in Sindanglaya Village in shaping the character of young people. The research applies a qualitative approach with communication and psychology methods. Data were collected from primary sources, including Karang Taruna leaders, village officials, Karang Taruna members, and community figures, as well as secondary sources such as interviews and documentation. The findings reveal that character development is conducted through sermon training, basic leadership training, and activities commemorating Independence Day. Internal factors supporting character formation include leadership performance, human resource quality, and financial support, while external factors consist of village government participation, external social influences, and parental support.